Primary spinal intradural extramedullary lymphoma: A novel management strategy. (January 2017) - Do, Angelique Sao-Mai; Smith, Gabriel A.; Pace, Jonathan; Hdeib, Alia; Kasliwal, Manish K.
Highlights: Primary spinal intradural extramedullary lymphoma is a rare entity requiring prompt diagnosis for medical decision-making. Lumbar puncture for cytopathologic diagnosis is efficacious if suspicion exists. Radiotherapy and medical management can be started quicker than if surgery is performed in non-emergent cases. Primary spinal intradural extramedullary lymphoma can carry a good prognosis with local control up 2 years from diagnosis. Abstract: Primary spinal intradural extramedullary lymphoma remains a very rare entity in spinal oncology. In this case report, we present the first treatment of a PSIEL diagnosed by cytopathologic analysis alone followed by urgent radio- and chemotherapy in the literature. At 18-month follow-up, our patient was ambulatory with near total imaging resolution of the lesion. In conclusion, surgical excision or biopsy may not be necessary when suspicion for PSIEL exists, and may delay prompt medical and radiation treatment due to necessity for wound healing. Further research into the management of extramedullary lymphoma treatment strategies is warranted.